Phase Only Antenna Pattern Notching Via a Semidefinite Programming Relaxation - Kajenski, P. J. (IEEE transactions on antennas and propagation, 2012)
A phase-only method of generating notches in the beam pattern of a phased array antenna is described. It is shown how the problem can be formulated as a semidefinite programming problem, and solved with readily available solvers. Numerical results simulating the performance of a 32 element uniform linear array are presented.